2021
DOI: 10.1029/2021ja029155
|View full text |Cite
|
Sign up to set email alerts
|

Ion Heating in the Polar Cap Under Northwards IMF Bz

Abstract: Joule heating in the polar cap F-region ionosphere is a significant factor in magnetosphere-ionosphere coupling. Magnetic reconnection between the interplanetary magnetic field (IMF) and the Earth's magnetosphere drives strong plasma convection across the entire polar region (Dungey, 1961). A relative velocity between ionized species and neutral species increases collisions between the two and heats both the plasma and neutral populations (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The extreme event described by Clauer et al [2016] shows an example where the ionospheric potential does not saturate and RISR-N observed >3 km/s drifts. While this event involved rare solar wind conditions, a larger survey of the RISR-N database 2010-2020 showed that RISR-N most frequently observes enhanced ion temperatures from Joule heating in the noon sector during northwards IMF conditions, which is consistent with lobe reconnection being the most common driver of significant Joule heating [Lamarche et al, 2021].…”
Section: Reconnection and Solar Wind -Magnetosphere -Ionosphere Couplingmentioning
confidence: 61%
See 1 more Smart Citation
“…The extreme event described by Clauer et al [2016] shows an example where the ionospheric potential does not saturate and RISR-N observed >3 km/s drifts. While this event involved rare solar wind conditions, a larger survey of the RISR-N database 2010-2020 showed that RISR-N most frequently observes enhanced ion temperatures from Joule heating in the noon sector during northwards IMF conditions, which is consistent with lobe reconnection being the most common driver of significant Joule heating [Lamarche et al, 2021].…”
Section: Reconnection and Solar Wind -Magnetosphere -Ionosphere Couplingmentioning
confidence: 61%
“…Unlike GDC, RISR has the ability to provide complete altitude profiles, to construct complete volumetric images, and to track the evolution of density structures in space and time. GDC will also greatly enhance RISR science by providing measurements of F-region neutral winds, which are a major uncertainty in interpreting frictional heating events [Lamarche et al, 2021].…”
Section: Future Coordination With Space-based Missionsmentioning
confidence: 99%
“…As with IPWM, HIDRA can be run as a stand‐alone model provided any correctly formatted input file containing specifications for high‐latitude energetic particle precipitation and electrostatic potential patterns. For example, (Lamarche et al., 2021), drove IPWM with precipitation patterns from the Ovation Prime empirical model (Newell et al., 2009) and electrostatic potential patterns derived from convection maps measured by the Super Dual Auroral Radar Network (SuperDARN) (Chisham et al., 2007; Greenwald et al., 1995; Nishitani et al., 2019). Misalignments between particle precipitation boundaries and convection boundaries can produce spurious Joule heating patterns.…”
Section: Model Description and Simulation Setupmentioning
confidence: 99%
“…These are often connected to flux transfer events and time-varying magnetic reconnection at the magnetopause (Moen et al, 2004;Lockwood et al, 2005). These flow channels have been connected to dramatic heating events (Lamarche et al, 2021), but without comprehensive and detailed observations of both flows and plasma temperature throughout the high latitude region, it is difficult to characterize how significant mesoscale Joule heating events are to the global energy budget.…”
Section: Joule Heatingmentioning
confidence: 99%